Fatigue property and microstructure deformation behavior of multiphase microstructure in a medium-carbon bainite steel under rolling contact condition. (August 2019) - Li, Qiangguo; Huang, Xuefei; Huang, Weigang
Highlights: The multiphase microstructure obtained by B-QP process shows better RCF properties. The B-QP steel with multiphase microstructure exhibits the better wear resistant. The multiphase microstructure has higher hardness increasing ratios after RCF test. The multiphase microstructure shows the larger strain accumulation under RCF test. The RCF damage level of the multiphase microstructure is lower. Abstract: Bainitic steel is considered to be the best potential candidate steel for rails due to its high strength and excellent toughness. The objective of this work was to investigate the fatigue property and microstructure deformation behavior of a medium-carbon bainitic steel with bainite/martensite/retained austenite multiphase microstructure obtained by a modified Q&P process (B-QP) under rolling contact condition. The analysis results of TEM indicated that the multiphase microstructure consists of lath bainitic ferrite, lath martensitic ferrite and film-like retained austenite which distributes mainly between bainite and martensite laths. The results showed that the multiphase microstructure has a better combination of toughness (103 J), hardness (47.8 HRC) and elongation (18.6%), along with better rolling contact fatigue (RCF) properties and wear resistance than that of full bainite microstructure obtained by the austempering process (BAT). After the steel subjected to 10 5 cycles of RCF testing, nanocrystalline grains (approximately 93 nm and 67 nm for the BAT and B-QP sample, respectively) were obtained at the deformed layer depth of 10 μm. Meanwhile, the multiphase microstructure demonstrated a higher microhardness increasing ratio (24.5%) than that of the full bainite (21.2%) and a larger plastic deformation zone (103 μm). The EBSD and XRD analysis indicated that the multiphase microstructure has a lower stress concentration possibility and higher percentage of high-angle boundaries as well as some film-like austenite retained in the plastic deformation layer. In addition, many pits on the contact surface of the BAT sample appeared, due to spalling damage caused by cyclic loading, and the crack propagation depth was larger. Conversely, the contact surface of the B-QP sample with a multiphase microstructure looked smooth, and the crack propagation depth was shallow under the contact surface. The enhanced rolling contact fatigue properties and wear resistance of multiphase microstructure can be mainly attributed to better a combination of strength and toughness, larger plastic strain accumulation and lower fatigue damage level.